Fine arts alumni reflections on curriculum and coursework in relation to global arts education: a social realist case study - Pather, Melvin (School of Education, 2025)
This dissertation aims to provide a legitimate investigation into whether the Fine Arts Degree effectively prepares students for successful integration into creative careers and the globalised arts industry. This research develops a case study by utilising alumni feedback data and curriculum information that is analysed to reflect on the student experiences in relation to the curriculum and coursework offered by the Michaelis School of Fine Art at the University of Cape Town. The data is examined within a social realist paradigm with reference to global arts educational practices and trends. Archer's Morphogenetic theory and Maton's Legitimation Code Theory is used as theoretical frameworks to elaborate on the curriculum experiences, the coursework changes and progression of the Fine Art department over a timeline of the last decade (2012 – 2022). The Fine Arts industry is a local and international hub of creative output and positions itself as a network of opportunities, gallery support, exhibitions, and art residencies. However, this research dissertation establishes that students completing Fine Art qualifications feel inadequate or misinformed by their studies in order to pursue sustainable creative careers in this industry. The analysis of alumni responses indicates the missing gaps in the Fine Arts curriculum and establishes the need for recommendations to the curriculum. Important aspects for consideration are the introduction of business in arts subjects as well as educating students on creative technologies, cross-disciplinary collaboration, and networking opportunities in the arts industry in line with other tertiary arts educational institutions.